Brands, tastes, judgements - Paraszt, Márta (Acta Carolus Robertus, 2022)
Selective bias is the tendency to interpret information in ways that are consistent with our preconceived notions. If, for example, consumers have different opinions about branded and non-branded versions of certain products, it can also be caused by the fact that they perceive the product differently due to their beliefs about the brand in any way (e.g. previous experience, brand name). With the involvement of several food industry products, I tested the relationship between the brand and perceived taste on two independent groups. During a blind test, I researched whether the favored branded product is really more tastier, and I used the brand test to check the effect of brand awareness on taste.